Implementasi Notifikasi Realtime pada Aplikasi Informasi Akademik Berbasis Android menggunakan Metode Agile - Nurul Amalia; Bambang Ismanto; Muhammad Faizal Kurniawan; Dicke Junryan Saut HS (STMIK Budi Darma, 2022)
In providing information to students, STMIK Widya Pratama Pekalongan has an LMS (Learning Management System) application in which there is information about curriculum, class schedules, KRS, finance and others. One of the most important features of the application is the latest news. Through this feature, students can see the latest news or information related to lectures such as activity information, payment information, lecture information, thesis submissions, and so on. Some of the information given to students is urgent, for example, information about submitting a thesis title in which there is a deadline that must be met for submitting the thesis title. Therefore, students must read the information as soon as possible after the information is sent. However, many students cannot immediately receive this information because they have not accessed the existing LMS application, so students cannot submit their thesis titles due to delays in accessing this information. Web-based information systems also make students rarely access applications because it is considered impractical to have to use a web browser to open them. This Academic Information Application with Android-Based Realtime Notifications uses an agile method with an extreme programming approach. This approach tries to simplify the stages in the software development process so that it becomes more flexible. From the research conducted, this academic information application makes it easier for students to access academic information without using a browser. This application can also provide notifications quickly to students when new information is sent, so that student academic activities can run smoothly.